A subset of patients with acquired partial lipodystrophy developing severe metabolic abnormalities. (3rd April 2019) - Ozgen Saydam, Basak; Sonmez, Melda; Simsir, Ilgin Yildirim; Erturk, Mehmet Sercan; Kulaksizoglu, Mustafa; Arkan, Tugba; Hekimsoy, Zeliha; Cavdar, Umit; Akinci, Gulcin; Demir, Tevfik; Altay, Canan Tuncer; Mihci, Ercan; et al.
ABSTRACT: Purpose/Aim of the study : Acquired partial lipodystrophy (APL) is a rare disease characterized by selective loss of adipose tissue. In this study, we aimed to present a subset of patients with APL, who developed severe metabolic abnormalities, from our national lipodystrophy registry. Materials and Methods : Severe metabolic abnormalities were defined as: poorly controlled diabetes (HbA1c above 7% despite treatment with insulin more than 1 unit/kg/day combined with oral antidiabetics), severe hypertriglyceridemia (triglycerides above 500 mg/dL despite treatment with lipid-lowering drugs), episodes of acute pancreatitis, or severe hepatic involvement (biopsy-proven non-alcoholic steatohepatitis (NASH)). Results : Among 140 patients with all forms of lipodystrophy (28 with APL), we identified 6 APL patients with severe metabolic abnormalities. The geometric mean for age was 37 years (range: 27–50 years; 4 females and 2 males). Five patients had poorly controlled diabetes despite treatment with high-dose insulin combined with oral antidiabetics. Severe hypertriglyceridemia developed in five patients, of those three experienced episodes of acute pancreatitis. Although all six patients had hepatic steatosis at various levels on imaging studies, NASH was proven in two patients on liver biopsy. Our data suggested that APL patients with severe metabolic abnormalities had a more advanced fat loss and longer disease duration. Conclusions : We suggest that these patients represent a potential subgroup of APL who may benefit from metreleptin or investigational therapies as standard treatment strategies fail to achieve a good metabolic control.